Dipterocarp seedling population dynamics in Bornean primary lowland forest during the 1997-8 El Niño-Southern Oscillation - Bebber, D; Brown, N; Speight, M (Cambridge University Press, 2004)
Dipterocarp seedling populations arising from a 1996 mast fruiting in closed-canopy primary lowland rain forest in Sabah, Malaysia, were monitored through the 1997-8 El Niño event to investigate the effects of drought and other factors on dipterocarp regeneration. Of particular interest was the influence of herbivory and its relation to drought, since water stress is known to influence herbivore performance. For seedlings with less than 10% leaf damage, mortality during a 6-mo period spanning the driest part of the drought was three times higher than mortality in the previous and subsequent 6-mo periods (~10% vs. ~30%). Leaf production was also higher during this period. Survival was positively related to leaf number and negatively related to leaf damage. Dryobalanops lanceolata was the tallest and leafiest species, and had low levels of leaf damage. Depending on sample period, abscission of leaves with more than 50% damage was between two and three times more likely than those with less than 10% damage. Mortality of seedlings defoliated by more than 50% was around twice that of seedlings defoliated by less than 10%. However, fewer than 10% of seedlings were defoliated by more than 50% at any time. The effect of defoliation did not seem to be altered by drought. Defoliation levels increased after the drought, perhaps due to a resurgence of insect populations. Drought may become a more important influence on dipterocarp regeneration in future, since El Niño events are thought to be increasing in frequency.